Disappearance of fat body proteins during soldier differentiation in the neotropical termite Heterotermes tenuis (Isoptera: Rhinotermitidae) - Laranjo, Lara Teixeira [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Springer, 2015)
Termites are social insects with well-defined castes: workers, soldiers and reproductives. The soldier is a terminal stage and originates from either larvae or workers after two molting processes that include an intermediate presoldier instar. The present study followed the occurrence and morphological changes of the fat body during the soldier ontogeny in the neotropical termite Heterotermes tenuis. Workers and soldiers collected in the field and presoldiers obtained in laboratory were fixed in FAA fixative and embedded in resin for light microscopy. The histological sections were submitted to histochemical tests for protein and urate detection. The fat body in all the individuals showed only two cellular types: adipocytes and urocytes. The adipocytes of presoldiers displayed some lipid droplets, and a large amount of acidophilic granules interpreted as proteins because they were strongly stained by xylidine Ponceau. In soldiers, the fat body was deprived from proteins and showed a higher quantity of urocytes with many urate spherocrystals compared with those present in workers and presoldiers. The results were consistent with metamorphosis process and with the possibility of presoldiers being at the beginning of molting stage. The occurrence of many protein granules suggests uptake and consumption of protein storage during the whole development of the presoldiers into soldiers. The dynamic transformations of the fat body enable the individuals of different phenotypes to accomplish their role in the termite colony.
Keywords: Adipocytes; Urocytes; Caste differentiation; Subterranean termite